Canavanine Content and Toxicity of Raw and Treated Bitter Vetch (Vicia ervilia) Seeds for Broiler Chicken - Sadeghi, Gh.; Samie, A.; Pourreza, J.; Rahmani, H.R. (International Journal of Poultry Science, 2004)
This study was conducted to determine canavanine content and examine the efficacy of soaking in water, acetic acid or heat treatments on the detoxification of bitter vetch for broiler chickens. A total of 1280 one-day old broiler chicks were placed in 64 pens, twenty in each pen. Treatments were included a corn -soybean based diet as control; raw bitter vetch; soaked in water (1:5, wt/vol) for 12 h, autoclaved (121oC, 20min), then dried at room temperature (SAD); coarsely ground, soaked in water for 24 h, autoclaved and dried (GSAD); coarsely ground, soaked in water for 47 h with exchange of water every 12 h, cooked (75min at 95oC) and dried (GSCD); coarsely ground, soaked at 1% Acetic acid solution for 24h at 60oC (GAAS) bitter vetch in three levels (15, 30, 45%). Each treatment replicated four times. Raw bitter vetch was contained 0.073 percent canavanine. All processing methods reduced canavanine content of seeds to a negotiable amount. Feeding of GSCD and GSAD diet resulted to higher and lower body weight (BW), feed intake (FI) and feed efficiency ratio (FER) at 21, 42 and 49 days, respectively, than other detoxification methods (P